Bone-associated gene evolution and the origin of flight in birds. (December 2016) - Machado, João; Johnson, Warren; Gilbert, M.; Zhang, Guojie; Jarvis, Erich; O'Brien, Stephen; Antunes, Agostinho
Abstract Background Bones have been subjected to considerable selective pressure throughout vertebrate evolution, such as occurred during the adaptations associated with the development of powered flight. Powered flight evolved independently in two extant clades of vertebrates, birds and bats. While this trait provided advantages such as in aerial foraging habits, escape from predators or long-distance travels, it also imposed great challenges, namely in the bone structure. Results We performed comparative genomic analyses of 89 bone-associated genes from 47 avian genomes (including 45 new), 39 mammalian, and 20 reptilian genomes, and demonstrate that birds, after correcting for multiple testing, have an almost two-fold increase in the number of bone-associated genes with evidence of positive selection (~52.8 %) compared with mammals (~30.3 %). Most of the positive-selected genes in birds are linked with bone regulation and remodeling and thirteen have been linked with functional pathways relevant to powered flight, including bone metabolism, bone fusion, muscle development and hyperglycemia levels. Genes encoding proteins involved in bone resorption, such asTPP1, had a high number of sites under Darwinian selection in birds. Conclusions Patterns of positive selection observed in bird ossification genes suggest that there was a period of intense selective pressure to improve flight efficiency that was closely linked with constraints on body size.